Die Kompression des Nervus medianus durch ein luxiertes Mondbein aufgrund eines karpalen Kollapses = Compression of the median nerve by chronic palmar dislocation of the lunate due to carpal collapse - Spies, Christian; Unglaub, Frank (Der Unfallchirurg, 2017)
Carpal tunnel syndrome is among the most frequently diagnosed forms of peripheral nerve compression. Carpal tunnel syndrome due to carpal collapse that had progressed over decades, with a palmarly dislocated lunate, is rare. Hints of past trauma to the wrist going back decades should prompt further radiological examination in case of recurrent median nerve compression. With sufficient preoperative evaluation, the causes can be accurately detected and treated. Therefore, precise and complete history-taking is mandatory. Conclusions on further diagnostics that can be drawn from the latter must be consistently implemented to enable adequate therapy.